A SYSTEMATIC REVIEW OF THE IMPACT OF INCENTIVES ON JOB PERFORMANCE AMONG HEALTHCARE WORKERS IN AFRICA - Ukponahiusi, Owie; Ahuru, Rolle Remi (African Journal of Social and Behavioural Sciences, 2025)
Africa has a weak health system, and one of the motivating factors for an effective health system is a poorly motivated workforce that is dissatisfied with their jobs. This study undertook a systematic review of studies that examined the impact of rewards on the motivation of healthcare workers in Africa. Electronic databases were searched for peerreviewed articles published in English with full-text retrieval within the period 2000-2023. Databases searched included Google Scholar, PubMed, Medline, and African Journals on Line (AJOL). The initial search gave rise to 984 articles retrieved from the databases. After screening, seventeen articles were included in the review. Three broad themes with sub-themes were identified, and they include financial incentives, organizational factors, and contingent rewards. Financial incentives, increments in salary, promotion with salary increments, pay-forperformance, cash bonuses, health and hazard allowances, and fringe benefits motivate healthcare workers. The study noted that salary is the strongest reward that motivates healthcare workers in Africa. Contingent rewards show that appreciation, recognition, and acknowledgement inspire workers into better performance and create job satisfaction. Organization-related factors that influence the behaviour of healthcare workers include the working conditions, the nature of the job, job autonomy, engagement, empowerment, supportive supervision, and an effective leadership approach. The study reported a high level of dissatisfaction among healthcare workers in Africa. In order to motivate healthcare workers, governments of African countries must strive to upgrade the salary structure, ensure that workers are regularly promoted, and improve work conditions. Improvements in work conditions entail creating enabling work environments, establishing flexible work schedules, and creating an atmosphere for cooperation, open communication, and interdependency among healthcare workers. Efforts should be made to provide adequate resources, equipment, and health infrastructure, and governments of African countries must strive to increase the number of health personnel per 1000 of the African population.